Applying GÃ©rard Genette’s Focalization Theory to Jinn: A Study of Fear Construction with Implications for AI-Based Narrative Interpretation - Rifzi Zulkarnain; Dedi Supriadi; Rohanda (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2026)
This study examines the construction of fear in the Arabic television series Jinn through GÃ©rard Genette’s theory of focalization. Employing a qualitative descriptive approach, the research analyzes four selected scenes using purposive sampling. Data were collected through observation and documentation, focusing on dialogue, visual narration, camera perspective, and character expressions. The analysis applies Genette’s three focalization categories, zero, internal, and external focalization, to identify how narrative information is distributed and how fear is constructed through perspective. The findings reveal that zero focalization establishes anticipatory fear by providing the audience with information unavailable to the characters, internal focalization intensifies psychological fear through restricted perception, and external focalization generates suspense by limiting access to characters’ inner states. These findings demonstrate that fear in Jinn is primarily produced through narrative information management rather than the mere presence of supernatural elements. Beyond contributing to Arabic narratology, this study offers conceptual insights for AI-based narrative interpretation by highlighting focalization as a systematic framework for detecting narrative perspective, information distribution, and emotional construction in audiovisual narratives.